Synthesis of cellulose-copper nanoparticle (cCMF/CuNPs) hybrid material for photodegradation of Congo red dye - Leal, Maria Vitória Guimarães [UNESP]; Gomes, Andressa Silva [UNESP]; Tolosa, Gabrieli Roefero [UNESP]; Bachmann, Cristian; Dognani, Guilherme [UNESP]; Osorio-Román, Igor; Job, Aldo Eloizo [UNESP] (Springer Nature, 2024)
Water contamination is an alarming problem, one of the main causes is the textile industry since about 20% of the dyes used during the production process are released into the environment. Congo red dye (CR) is widely used, however, in contact with humans, it can be harmful. An effective alternative treatment of dyeing wastewater is photodegradation by hybrid materials. Cellulose is an abundant, biodegradable, and hydrophilic polymer that united to properties of copper nanoparticles (CuNPs) synthesis as low cost is a great proposal to create a potential photocatalytic material. In the present work, a new green synthesis of CuNPs on cationic cellulose microfibers (cCMF) surface is proposed. The synthesis was executed at three different pH (4.5, 7.5, and 10.5) and the photodegradation tests were performed under three different light sources (white light, UV lamp, and a 515 nm laser). Each excitation source exerts distinct effects on the different nanoparticles. This study represents the first instance in the literature where both the excitation source and the synthesis pH were systematically assessed together to determine their respective impacts on photodegradation efficiency. The findings reach a pH 4.5 more effectively under white light, pH 7.5 under the UV lamp, and pH 10.5 under the laser, these results are due to the absorption capacity of each hybrid material. However, in all cases, the photodegradation of CR presented greater results with the cCMF/CuNPs than without it, proving that the hybrid material worked as a catalytic agent applied to CR photodegradation. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Cationic dialdehyde cellulose; Cellulose; Congo red dye; Copper nanoparticles; Microfibers; Photodegradation